Essays on stop-loss rules : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Finance at Massey University, Palmerston North, New Zealand - Dai, Bochuan (Massey University, 2021)
Stop-loss rules are trading rules that involve selling a security when its price drops by a certain amount and buying the security back when its price rises above a pre-specified level. They are popularly used by practitioners. These rules are designed to protect gained profits as their sale trigger the price to be adjusted higher as prices increase. This thesis contributes to the literature on stop-loss rules in financial markets. The first essay investigates the time-series and cross-sectional determinants of stop-loss rules for risk reduction in the U.S. stock market. It finds that, even though stop-loss rules have poorer mean returns to a mean-variance optimal benchmark, they are effective at stopping losses. These rules reduce overall and downside risk, especially during declining market states. The transaction costs analysis shows that the significant effectiveness of risk reduction holds for these rules with larger stop-loss thresholds. Essay two examines the performance of stop-loss rules from the perspective of international equity market allocation. International diversification provides potential for larger returns but often induces higher risks. Thus, it is a natural setting to consider stop-loss rules from a global point-of-view. This essay finds that stop-loss rules are an important factor of international equity allocation in a parametric portfolio policy setting. These rules generate portfolios with larger mean and risk-adjusted returns. This result is economically stronger in declining markets. The outperformance is robust once the transaction costs are accounted for. Essay three shows that stop-loss rules enhance the returns to stocks with lottery features. Individual investors have a strong preference for lottery stocks that typically have irregular enormous gains and frequent small losses. Stop-loss rules are useful at reducing losses and protecting gains from large price rises. This essay highlights that the sell signals of popular technical rules and time-series momentum rules are consistent with stop-loss rules, thereby effectively increasing the risk-adjusted returns of lottery stocks. These rules would have helped investors avoid instances of major historical drawdowns and are particularly beneficial in recessionary markets. Some rules are robust to the inclusion of transaction costs.
Keywords: Stock exchanges; Stocks; Prices; 350208 Investment and risk management